KEWIRAUSAHAAN: MENGATASI TANTANGAN FINANSIAL PENDIDIKAN - , Maryati; Setiadi; Solihin, Dadin (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2022)
This research aims to discuss the financial challenges in access to education that hinder individuals from various economic backgrounds. Qualitative research approach with case study method. The data comes from teaching staff/lecturers, students/students, and the Regional Government. All data was collected using data collection techniques. This article explains that entrepreneurship emerges as an innovative solution by utilizing creativity, the spirit of innovation, and entrepreneurial skills to create business opportunities, overcome financial obstacles, expand access to education, increase individual financial independence, and support broad educational inclusion in society.